Magnetic Induction Tomography (MIT) simulation study for renal screening using different system frequencies and sizes of calcium oxalate - Paulus, Thompson (2020)
Nephrolithiasis is the process of forming stone in the kidney by crystallization. Due to the increasing prevalence of nephrolithiasis from time to time, medical institutions look for more advanced technology of medical imaging which can tackle the disadvantages of current medical imaging devices for renal, which are non-invasive, free radiation and rapid use. The research encompassed the design simulation study of Magnetic Induction Tomography (MIT) system for renal screening by using COMSOL multiphysics. MIT is a soft field tomography and a non-contact imaging modality used to image the passive electromagnetic properties (conductivity, permittivity and permeability) by applying principle of electromagnetic induction. In this research, 8 copper trans-receiver coils were employed in the MIT system and fixed by the insulation belt. Meanwhile, geometric set-up of renal organ imitates the transverse section at renal level of human body. Sensor performance analysis of MIT system was done based on various frequency and radius of calcium oxalate inside kidneys. In conclusion, frequency and radius of calcium oxalate affect the sensitivity performance of MIT system and has inverse relationship with sensitivity performance.